PENGARUH KOMPOSISI CAMPURAN LIMBAH PADAT DAN CAIR INDUSTRI TAPIOKA TERHADAP PERSENTASE PENYISIHAN TOTAL SUSPENDED SOLID (TSS) DENGAN STARTER KOTORAN SAPI - Syervy Tanata; Mimi Richell Gunawan; Setiaty Pandia (Talenta Publisher (Universitas Sumatera Utara), 2013)
The waste from tapioca industry is classified as an organic waste that contains many important compounds such as carbohydrate, protein and glucose. The research is aimed to know the quality of biogas from cassava pulp combined with waste water from the cassava starch industry using batch anaerobic digester system. The research began by mixing the solid and liquid wastes from tapioca industry at ratio 70:30; 60:40; 50:50; 40:60; and 30:70 (w/w) with starter from solid waste of cattle in a batch anaerobic digester. From this research, the optimum percentage reduction of Total Suspended Solid (TSS) was 76,2289% at ratio of solid and liquid waste was 70:30 (w/w).